World Workshop on Oral Medicine VII: Clinical evidence of differential expression of lncRNAs in oral squamous cell carcinoma: A scoping review. (29th May 2019) - Pentenero, Monica; Bowers, Leah M.; Jayasinghe, Ruwan; Yap, Tami; Cheong, Sok Ching; Kerr, Alexander R.; Farah, Camile S.; Alevizos, Ilias
Abstract: Background: Long non‐coding RNAs (lncRNAs) have important roles in regulating gene expression pertaining to cell proliferation, survival, migration and genomic stability. Dysregulated expression of lncRNAs is implicated in cancer initiation, progression and metastasis. Objectives: To explore, map and summarize the extent of evidence from clinical studies investigating the differential expression of lncRNAs in oral/tongue squamous cell carcinoma. Methods: PubMed, Scopus and Web of Science were used as search engines. Clinical, full‐length, English language studies were included. PRISMA‐ScR protocol was used to evaluate and present results. The present scoping review summarizes relationships of the differential expression of lncRNAs with the presence of tumour and with clinicopathological features including survival. Results: Almost half of the investigated transcripts have been explored in more than one study, yet not always with consistent results. The collected data were also compared to the limited studies investigating oral epithelial dysplasia. Data are not easily comparable, first because of different methods used to define what differential expression is, and second because only a limited number of studies performed multivariate analyses to identify clinicopathological features associated with the differentially expressed lncRNAs. Conclusions: Standard methods and more appropriate data analyses are needed in order to achieve reliable results from future studies.